Oil in the Gulf of Guinea States and South Africa in the Matrix of Overlapping Membership of African Regional Communities: An Impediment to Regional Integration? - Jobodwana, Zingisile Ntozintle (Journal of Law, Society and Development, 2016)
The Gulf of Guinea states (GOGs) discussed in this article comprise a diverse group of more than 20 African states bordering on the oil-rich Gulf of Guinea. They are former colonies of Belgium, France, Great Britain and Germany. These states are of strategic importance to the United States, the European Union, India and China because of their tremendous natural resources that include biodiversity, oil, gas and other strategic minerals. But to what extent are they also of strategic importance not only to South Africa but to SADC member states? After all, the GOGs boast of their sea routes being safer and more convenient for sea transport. Post-colonial independence finds these states still adopting a mixture of foreign legal systems side by side with indigenous laws and customs. The region is still underdeveloped, with poor physical infrastructure, weak government structures, an inefficient legal system, and internecine strife and other inter-state disputes exerting a debilitating influence. The NEPAD Plan of Action of 2001 looks to the regional economic communities (RECs) to become the leaders in regional economic co-operation and integration. Although the GOGs are characterised at present by overlapping membership of various communities, they have enjoyed some successes based on the newly found petroleum commodity which, wisely managed, can help to increase intra-African trade and produce a viable extensive African market buttressed by South Africa's economic advances into the rest of Africa. In some of the regions in Africa RECs such as ECOWAS and SADC have been able to transform their economic and monetary co-operation efforts into a powerful driving force for economic policy co-ordination and integration, but a strong, credible, effective and efficient legal framework with sustainable supporting institutions is now needed. South Africa is well poised to assist with deepening the political and economic integration in the GOGs by intensifying foreign direct investment (FDI), capacity-building and training projects, and the transfer of skills and technology. But the RECs overlapping membership needs to be rationalised, the negative influences of the superpowers need to be resisted, and support is required to maintain peace and stability and ensure the security of the maritime regimes. A strong, independent supra-national body that is also able to supervise and monitor revenues from oil for the benefit of the region as a whole should be established.
Keywords: African Union; COMESA; EAC; ECCAS; ECOWAS; Gulf of Guinea Commission; Gulf of Guinea states; OHADA; Overlapping membership; Regional economic communities (RECs); Regional integration; SACU; SADC; South Africa; Supra-national independent regiona; Treaties

Risques et responsabilité civile en matière d'installation pétrolière offshore - Troussier, Julie (Aix-Marseille Université, 2016)